Transformative career maturity training for rural adolescents: an exploratory approach - Pooja Damodar; Ankitha Shetty; Arjun Prakash; Komal Jenifer Dsouza (International Journal of Adolescence and Youth)
Rural adolescents often overlook the significance of early career preparation, thus hampering their school-to-college transition. Regardless of overall growth, Karnataka, a state in India, confronts challenges in achieving a high transition rate, and a paucity of career maturity among rural youth exists. Recognizing a dire need to explore effective interventions for promoting career maturity, the study designed and demonstrated training among 76 Tenth-grade students from rural government schools. Qualitative questionnaires and focus group discussions elucidate the perceived impact of training on career maturity and identify the influence of career barriers and supports. Thematic and content analysis revealed an improved career outlook among participants by boosting career concern, curiosity, confidence, and control while alleviating career anxieties. Nevertheless, the findings uncovered persistent gender disparities. Exploration of models’ benefits and potential improvements informed the design of comprehensive training that facilitates early rural career development. The implications extend to policy, practice, and further research.